Prospect of Petroleomics as a Tool for Changing Refining Technologies - HAYASAKA, Toshiaki; NAKAMURA, Tsutomu; INAMURA, Kazuhiro; TAKAHASHI, Yuuki; TOYOOKA, Yoshiyuki; SATO, Koichi; KATANO, Keita; TSUJI, Koji (Journal of the Japan Petroleum Institute, 2020)
Japan Petroleum Energy Center (JPEC) and partners have been developing “Petroleomics” as a new refining technology since 2011. Petroleomics can be a technology to achieve the ultimate method based on molecular reaction models with molecular level analyses of heavy oil. After the fundamental stage taking five years, our petroleum informatics database includes more than 25 million chemical structures of heavy oil components constructed with the aid of Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS). Subsequently, reaction modeling studies were applied to residue hydrodesulfurization (RDS) and the aggregation model for asphaltenes to sediments, both of which are particularly important subjects in heavy oil upgrading. Our Petroleomics project is now in the application stage to attempt three major investigations: a molecular database of crude oils including unconventional oils, total optimization of RDS and residue fluid catalytic cracking (RFCC) operations with reaction modeling, and the mechanism of asphaltene aggregation responsible for fouling and plugging in some heavy oil upgrading processes. Further progress in Petroleomics is expected to achieve practical applications in refineries, such as advanced performance diagnosis, operational optimization, and catalyst and process development.